Industrial revolution 4.0: What should be prepared for the next stage? - Adya Herawati; Suhermin Suhermin; Hastin Umi Anisah; Roby Sambung (Jurnal Inovasi Ekonomi, 2021)
This article aims to analyze the opportunities and challenges in the era of the industrial revolution 4.0. This research is a descriptive study with a qualitative approach and uses the literature study method. This study indicates that the opportunities in the era of the industrial revolution 4.0 are in the industrial ecosystem, which is increasingly open, and the challenges are focused on the readiness of human resources. This study formulates that to prepare competitive human resources in the era of the 4.0 industrial revolution, learning in tertiary institutions must be oriented towards a) inter-multi discipline; b) problem solving oriented; c) interpersonal skills, and d) innovation based on technology.